PENGARUH LEVERAGE TERHADAP AGRESIVITAS PAJAK PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI PERIODE 2020–2024 - Masta Sembiring (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This research is motivated by indications of tax aggressiveness practices among pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). One of the factors suspected to influence tax aggressiveness is leverage; however, previous studies have shown inconsistent findings, making it necessary to re-examine this relationship. This study aims to determine the partial effect of leverage on tax aggressiveness in pharmaceutical sub-sector companies listed on the IDX for the 2020–2024 period. The type of research used is quantitative research. The sampling technique employed is purposive sampling, resulting in a selection of companies that meet the specified criteria. Data were collected through documentation of annual financial reports obtained from the official IDX website. Data analysis was conducted using panel data regression with the assistance of E-Views 12 software. The results show that leverage does not have a significant effect on tax aggressiveness in pharmaceutical sub-sector companies. The coefficient of determination (R²) of 0.0216 indicates that leverage explains only 2.16% of the variation in tax aggressiveness, while the remaining 97.84% is influenced by other factors not included in this research model.